Medicinal plants from swidden fallows and sacred forest of the Karen and the Lawa in Thailand - Junsongduang A. (2014)
Background: Many ecosystem services provided by forests are important for the livelihoods of indigenous people. Sacred forests are used for traditional practices by the ethnic minorities in northern Thailand and they protect these forests that are important for their culture and daily life. Swidden fallow fields are a dominant feature of the agricultural farming landscapes in the region. In this study we evaluate and compare the importance of swidden fallow fields and sacred forests as providers of medicinal plants among the Karen and Lawa ethnic minorities in northern Thailand.Methods: We made plant inventories in swidden fallow fields of three different ages (1-2, 3-4, 5-6 years old) and in sacred forests around two villages using a replicated stratified design of vegetation plots. Subsequently we interviewed the villagers, using semi-structured questionnaires, to assess the medicinal use of the species encountered in the vegetation survey.Results: We registered a total of 365 species in 244 genera and 82 families. Of these 72(19%) species in 60(24%) genera and 32(39%) families had medicinal uses. Although the sacred forest overall housed more species than the swidden fallow fields, about equal numbers of medicinal plants were derived from the forest and the fallows. This in turn means that a higher proportion (48% and 34%) of the species in the relatively species poor fallows were used for medicinal purposes than the proportion of medicinal plants from the sacred forest which accounted for 17-22%. Of the 32 medicinal plant families Euphorbiaceae and Lauraceae had most used species in the Karen and Lawa villages respectively.Conclusion: Sacred forest are important for providing medicinal plant species to the Karen and Lawa communities in northern Thailand, but the swidden fallows around the villages are equally important in terms of absolute numbers of medicinal plant species, and more important if counted as proportion of the total number of species in a habitat. This points to the importance of secondary vegetation as provider of medicinal plants around rural villages as seen elsewhere in the tropics. © 2013 Junsongduang et al.; licensee BioMed Central Ltd.